The Reletionship between Hand Eye Coordination and Arm Muscle Strength with Upper Passing Ability in Volleyball Extracurricular Activities for Female Students of SMA Negeri 1 Tembilahan Hulu - Dona Juliana; devit wilastra (Jurnal Olahraga Indragiri, 2023)
This research is correlational, namely to determine the relationship between one variable and another. The population in this study were all female students at SMA Negeri 1 Temblahan Hulu who took part in volleyball extracurricular activities, totaling 15 students. While the sampling in this study used a total sampling technique, amounting to 15 female students. To obtain the research data, tests and measurements were carried out, namely the catch ball throwing test to measure hand-eye coordination (X1), the push-up test to measure arm muscle strength (X2) and to test upper passing ability in volleyball games (Y). From the results of the study, it was obtained that the multiple correlation coefficient rcount = 0.99 > rtable = 0.514 (the research hypothesis is accepted) and the correlation significance test (t distribution) shows tcount (2.56) > ttable (2.16) then Ho is rejected and Ha is accepted ( significant), and where the results of the determinant index are 90.01% and the r value is 0.99. From the results of this study it can be concluded that there is a significant relationship between Hand Eye Coordination and Arm Muscle Strength with Upper Passing Ability in Volleyball Extracurricular Activities for High School Female Students Negeri 1 Tembilahan Hulu, and has a very strong data interpretation.